2012
DOI: 10.1063/1.4753927
|View full text |Cite
|
Sign up to set email alerts
|

Studies on atomic layer deposition Al2O3/In0.53Ga0.47As interface formation mechanism based on air-gap capacitance-voltage method

Abstract: The air-gap capacitance-voltage characteristics of InGaAs surfaces were measured after 1-, 2-, 6-, 9-, and 17-cycle atomic layer deposition (ALD) Al2O3 processing. A high density of mid-gap states was found to be generated and increased during these ALD process steps, while the native oxide component was reduced. On the other hand, the mid-gap state density was drastically reduced after the usual annealing process. The generation of the mid-gap states seemed to be relevant to a non-stoichiometric Al-oxide comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…As reported in the literature [21][22][23][24], the ALD deposition of Al 2 O 3 results in the so-called ''clean up effect'', which consumes interfacial oxides during the initial stages of Al 2 O 3 growth, however, the extent of this effect depends on the initial oxide thickness. The observed changes in the As oxides with thermal anneal are in agreement with a recent XPS study by Yoshida et al [2] of the thermal annealing of ALD deposited Al 2 O 3 on the InGaAs surface which showed a decrease in higher oxidation arsenic states with increased temperature. The high temperature thermal anneals essentially leave both interfaces chemically identical in relation to the As 3d spectrum and there is no evidence of arsenic out diffusion.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As reported in the literature [21][22][23][24], the ALD deposition of Al 2 O 3 results in the so-called ''clean up effect'', which consumes interfacial oxides during the initial stages of Al 2 O 3 growth, however, the extent of this effect depends on the initial oxide thickness. The observed changes in the As oxides with thermal anneal are in agreement with a recent XPS study by Yoshida et al [2] of the thermal annealing of ALD deposited Al 2 O 3 on the InGaAs surface which showed a decrease in higher oxidation arsenic states with increased temperature. The high temperature thermal anneals essentially leave both interfaces chemically identical in relation to the As 3d spectrum and there is no evidence of arsenic out diffusion.…”
Section: Resultssupporting
confidence: 92%
“…Significant progress has been recently made in improving the electrical quality of the high-k dielectric-InGaAs interface by the atomic layer deposition (ALD) of high-k materials on passivated surfaces [1][2][3]. Controlling III-V surface oxidation, which leads to the formation of a high density of extrinsic defect states (D it ) at the high-k/InGaAs interface, is a major challenge to optimum device operation.…”
Section: Introductionmentioning
confidence: 99%
“…This may be contrary to the general understanding that the existence of the As 2 O 5 component may lead to the formation of the mid-gap states. 24) On the other hand, this result can support the author's previous model, 21) in which the oxygen deficiency in the self-cleaning period of the initial ALD process induces mid-gap formation, which can be made moderate by the existence of an adequate density of oxygen atoms in As 2 O 5 rather than in As 2 O 3 .…”
supporting
confidence: 83%
“…My research group has recently demonstrated the possibility that the native oxide/InGaAs interface behaves well 21) by layer-by-layer characterization in the initial stage of the ALD-Al 2 O 3 process using the air-gap capacitance-voltage (C-V) technique. 22,23) It is not yet certain whether it is important to fabricate clean surfaces in order to obtain a good interface, and the role of oxide components in the interface formation processes should be identified.…”
mentioning
confidence: 99%
“…5. 44,45) However, I D -V GS characteristics clearly show that the TFT properties can be improved, and a recent first-principles calculation also reveals that hydrogen passivation is effective for the reduction in the density of gap states in GaAs. 46) We consider that the schematic model well describes the phenomenon, since it is consistent with the result of electrical characterization.…”
Section: Tfts With Gaas Nw Random Network Channelmentioning
confidence: 99%